2020
DOI: 10.1183/20734735.0007-2020
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangioleiomyomatosis: a clinical review

Abstract: Lymphangioleiomyomatosis (LAM) is a diffuse cystic lung disease. There are two main types of LAM: sporadic, and LAM associated with the tuberous sclerosis complex (TSC), which is caused by mutations in the TSC1 and TSC2 genes. LAM is characterised by cystic lung disease resulting in progressive dyspnoea, renal angiomyolipomas and lymphatic complications. Pneumothorax occurs frequently (70%) and definitive management with pleurodesis is recommended as the risk of recurrence is high. Characteristic thin-walled c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 74 publications
1
24
0
1
Order By: Relevance
“…The efficacy of sirolimus has been demonstrated in patients with predicted FEV 1 value of 70% or less 8 , and with symptomatic chylothorax 11 . Other studies have suggested that patients with rapidly declining FEV 1 , reduced DL CO , exercise-induced or resting hypoxemia, angiomyolipomas or lymphangioleiomyomas might benefit from sirolimus 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of sirolimus has been demonstrated in patients with predicted FEV 1 value of 70% or less 8 , and with symptomatic chylothorax 11 . Other studies have suggested that patients with rapidly declining FEV 1 , reduced DL CO , exercise-induced or resting hypoxemia, angiomyolipomas or lymphangioleiomyomas might benefit from sirolimus 21 , 22 .…”
Section: Discussionmentioning
confidence: 99%
“…These patients, comprising nearly one-third of the study population, were associated with good baseline lung function, menopause at diagnosis, and absence of abdominal lymphadenopathy (Supplementary Table S3 ). Clinical manifestations of LAM are highly heterogeneous 21 . As seen in our study population (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Lymphangioleiomyomatosis (LAM) is a diffuse cystic lung disease predominantly affecting females of reproductive age [65]. It is sometimes associated with the tuberous sclerosis complex (TSC), which is caused by germline pathogenic variants in the TSC1 and TSC2 genes [65].…”
Section: Lymphangioleiomyomatosismentioning
confidence: 99%
“…Lymphangioleiomyomatosis (LAM) is a diffuse cystic lung disease predominantly affecting females of reproductive age [65]. It is sometimes associated with the tuberous sclerosis complex (TSC), which is caused by germline pathogenic variants in the TSC1 and TSC2 genes [65]. LAM is characterised by small thin-walled cysts throughout the lungs resulting in progressive dyspnoea and renal angiomyolipomas [64,65].…”
Section: Lymphangioleiomyomatosismentioning
confidence: 99%
See 1 more Smart Citation